2017
DOI: 10.5051/jpis.2017.47.5.273
|View full text |Cite
|
Sign up to set email alerts
|

Static magnetic fields promote osteoblastic/cementoblastic differentiation in osteoblasts, cementoblasts, and periodontal ligament cells

Abstract: PurposeAlthough static magnetic fields (SMFs) have been used in dental prostheses and osseointegrated implants, their biological effects on osteoblastic and cementoblastic differentiation in cells involved in periodontal regeneration remain unknown. This study was undertaken to investigate the effects of SMFs (15 mT) on the osteoblastic and cementoblastic differentiation of human osteoblasts, periodontal ligament cells (PDLCs), and cementoblasts, and to explore the possible mechanisms underlying these effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 39 publications
0
19
1
Order By: Relevance
“…Interestingly, weak‐to‐moderate intensity SMFs, particularly 15 mT, maximally inhibited RANKL‐induced osteoclast differentiation in vitro. This magnitude also showed the highest growth and osteoblastic differentiation of MSCs [Kim et al, ] and periodontium‐derived cells [Kim et al, ]. These results show that SMFs affected not only osteoblast function, but also osteoclast activity.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Interestingly, weak‐to‐moderate intensity SMFs, particularly 15 mT, maximally inhibited RANKL‐induced osteoclast differentiation in vitro. This magnitude also showed the highest growth and osteoblastic differentiation of MSCs [Kim et al, ] and periodontium‐derived cells [Kim et al, ]. These results show that SMFs affected not only osteoblast function, but also osteoclast activity.…”
Section: Discussionmentioning
confidence: 74%
“…A magnet was placed horizontally below the wells, and the north (N) side of magnet was oriented towards the well. We selected the same SMF intensities that were found to stimulate osteogenic differentiation in MSCs [Kim et al, ] and periodontium‐derived cells [Kim et al, ] in our previous studies. The SMFs were established by controlling the distance between the magnet and culture plates, as previously described [Kim et al, ; Kim et al, ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that the SMF had a positive effect on cell proliferation and gene expression. Kim et al also demonstrated a positive effect of moderate SMF (15 mT) on osteoblast differentiation and osteogenic gene expression and revealed that this was related to the activation of the Wnt, p38, c‐Jun N‐terminal kinase (JNK)/mitogen‐activated protein kinase (MAPK), and NF‐ ĸ B signaling pathways . Because this study focused only on four osteogenic genes, further investigation will be necessary to determine whether the doping of Fe ions in the HA matrix will affect the expression or the signaling pathways of other genes in order to clarify the reason(s) for the slow down in cell proliferation.…”
Section: Resultsmentioning
confidence: 93%
“…PEMF exposure increased the expressions of Wnt1, LRP5, and β‐catenin, as well as osteocalcin in both OVX and hindlimb‐suspended rat models, suggesting that PEMF may increase bone mineral density via activation of Wnt signaling pathway [Jing et al, 2013; Jing et al, 2014]. In addition, SMF has also been found to upregulate the expressions of Wnt proteins [Kim et al, 2017].…”
Section: Introductionmentioning
confidence: 99%